2012
DOI: 10.1007/s12262-012-0560-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cholecystocutaneous Fistula—Not an Old Time Story

Abstract: Cases of spontaneous cholecystocutaneous fistula continue to attend surgical outpatient department in-spite of tremendous improvement in early diagnosis and treatment of gallbladder disease. It occurs as a complication of acute suppurative cholecystitis or neglected chronic cholecystitis due to cholelithiasis. We report two cases of spontaneous cholecystocutaneous fistula due to chronic cholecystitis with review of literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
0
10
0
3
Order By: Relevance
“…Generally, the patient presents after a long duration of symptoms suspicious for cholecystitis, with an abscess or fistula in the right upper quadrant, though less common areas such as the epigastrium, umbilicus, and right groin have been described [2,3]. The majority of patients are over the age of 60 and have multiple medical comorbidities which can lead to a delay in presentation and diagnosis [1,[4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the patient presents after a long duration of symptoms suspicious for cholecystitis, with an abscess or fistula in the right upper quadrant, though less common areas such as the epigastrium, umbilicus, and right groin have been described [2,3]. The majority of patients are over the age of 60 and have multiple medical comorbidities which can lead to a delay in presentation and diagnosis [1,[4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Following stabilization, an open cholecystectomy with or without excision of the fistula tract may be performed [8,9]. For stable patients who may present with relatively few symptoms other than an abscess or draining fistula tract, a single stage definitive operation with external drainage and open cholecystectomy has been considered the treatment of choice [1,7,10]. A laparoscopic approach to this single-stage operation has been reported with success by several authors, though generally this is reserved for patients who have a more subacute presentation [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Orestis Ionaditis et al (2012) reported a case of spontaneous cholecysto-cutaneous fistula draining via an old surgical drain site scar [5]. Another such case was reported by Yamini Kapoor et al [6] in one of the two cases in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Son más habituales en pacientes ancianos o diabéticos, donde los síntomas de la patología biliar pueden ser inespecíficos y pasar desapercibidos. También se ha descrito asociación de la FCC con la poliarteritis nodosa, vasculitis, tratamiento con corticoides e infección por Salmonella typhi, que puede dar lugar a una colecistitis crónica 4 .…”
Section: Discussionunclassified